Pre-Retirement Product Marketing Strategy to Attract Public Interest : Case Study of Bank Syariah Indonesia KCP Lampung Barat - Okta Supriyaningsih; Nadhila Fitri (Lead Journal of Economy and Administration, 2025)
This study aims to analyze the marketing strategy of pre-retirement products implemented by Bank Syariah Indonesia KCP Lampung Barat to attract public interest. The research method used was a case study with a qualitative approach. Data were collected through in-depth interviews with the bank and potential customers, as well as through documentation. The results indicate that the implemented marketing strategy includes market segmentation, targeting productive age groups with awareness of future investment, and positioning as a safe and profitable Sharia financial solution for retirement preparation. The marketing mix implemented includes competitive products, affordable prices, promotions through social media and outreach activities, and strategic placement. This study also identifies factors influencing public interest in pre-retirement products, such as level of trust in Sharia banks, understanding of Sharia investments, and the need for future financial planning. This research provides practical implications for Bank Syariah Indonesia KCP Lampung Barat in improving the effectiveness of its pre-retirement product marketing strategy.